Robustness in combinatorial optimization and scheduling theory: An extended annotated bibliography - Yury Nikulin (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2006)
This work is an up-to-date-extension of a previous annotated bibliography (2004) which covered 40 references only. It focuses on what has been published during the last ten years in the area of combinatorial optimization and scheduling theory concerning robustness and other similar techniques dealing with worst case optimization under uncertainty and non-accuracy of problem data.
Keywords: 650; robustness; tolerance; worst-case scenario; input data uncertainty; non-accuracy; flexibility of solution; maximal regret; Scheduling-Verfahren; Robustes Verfahren; Theorie